Hydrological Changes Related to ENSO‐Like States During the Last Deglaciation in Central Eastern China. Issue 10 (5th October 2021) - Zhang, Wenchao; Dodson, John; Chang, Maoxiang; Li, Guangxue
Abstract: Present knowledge of hydrological changes in the East Asian summer monsoon region during the last deglaciation lacks precision, most especially for central eastern China. A hydrological reconstruction based on elemental ratios, such as Rubidium/Strontium (Rb/Sr) and Zirconium/Rubidium (Zr/Rb), and grain‐size distribution for the period of 22.8–7.4 ka was derived from the Dajiuhu basin in central eastern China. The reconstruction shows that there were some small wet‐dry fluctuations within the basin between 22.8 and 17.5 ka, but an abrupt wetting after 17.5 ka, with a maximum occurring around 15.0 ka, then a drying trend until the early Holocene. This pattern parallels the zonal gradient of sea surface temperature (SST) across the tropical Pacific, which suggests that wet conditions in the Dajiuhu basin respond to the decreased SST zonal gradient. A marked decrease in the tropical Pacific SST zonal gradient, seen as an El Niño‐like state, could lead to an anomalous anticyclonic circulation at the Western Pacific and a southward excursion of the Western Pacific Subtropical High, which favors the occurrence of wet conditions in central eastern China. Meanwhile, this El Niño‐like state could sharpen the SST meridional gradient between the tropics and the extratropics, and then shift the upper tropospheric westerlies southward, which in turn induces a prolonged Mei‐yu and more precipitation in central eastern China. Overall, it is concluded that the El Niño‐Southern Oscillation‐like states might be a major forcing for hydrological changes in central eastern China during the last deglaciation. Key Points: Hydrological reconstruction in the Dajiuhu basin shows an abrupt wet condition from 17.5 to 15.0 ka, then followed by a drying trend Our Dajiuhu records parallel the zonal gradient of sea surface temperature across the tropical Pacific during the last deglaciation El Niño‐Southern Oscillation‐like states might be responsible for hydrological changes in the Dajiuhu basin during the last deglaciation